Gebyar Budaya Desa Jetis 2022: Pelestarian Budaya Berbasis Cultural Experience - Indah Maryani; Dewi Lestari; Fadzilah Arisyandi; Indriyani Indriyani; Aleo Shelgy Agustin; Triyaka Triyaka; Ahmad Saeroji (Edumedia Solution, 2022)
Culture is a characteristic of a multicultural society which is the wealth of a nation. Culture as a heritage that is rich in noble and traditional values must be preserved as a nation's pride in the previous society. One of the cultural ways that can be done is through experience through this KKN UNNES holding the 2022 Jetis Village Cultural Festival. This Cultural Festival requires every community to display the culture of various regions. The method used is deliberation between the UNNES Community Service Center, Karang Taruna, and related village officials for problems from the previous cultural celebration, determining the theme of the cultural celebration and sharing the theme and socializing the cultural celebration system. The result of this study is the implementation of the 2022 Jetis village cultural celebration which was attended by approximately 800 participants with cultural themes from the provinces of Sumatra, Papua, Sulawesi, Jakarta, Kalimantan, NTT, East Java, and Central Java.